Proximal Femoral Nail Versus Proximal Femoral Locking Compression Plate in the Treatment of Unstable Trochanteric Fracture in Adults (Journal of Rangpur Medical College, 2026)
Background: Unstable trochanteric fractures are common in adults and require stable fixation to enable early mobilization and reduce morbidity. Proximal femoral nail and proximal femoral locking compression plate are frequently used implants, but direct comparative data from local clinical settings remain limited. Objective: This study compared operative, radiological, and functional outcomes between these two fixation methods. Methods: This cross-sectional analytical study was conducted in the Department of Orthopaedic Surgery, Sylhet M.A.G. Osmani Medical College Hospital, Sylhet from January 2017 to December 2018. Twelve adults with unstable trochanteric fractures were enrolled and allocated equally to nail or plate fixation. After clinical assessment and informed consent, fixation was performed as per group allocation. Patients were followed for 24 weeks, assessing operative variables, mobilization milestones, radiological union, complications, and functional outcome using the Harris Hip Score. Statistical significance was set at p